2003
DOI: 10.1016/s0002-9440(10)64303-9
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Transgenic Skeletal Muscles with Altered Timing of Expression of the Basic Helix-Loop-Helix Muscle Regulatory Factor MRF4

Abstract: In regenerating muscle cells, muscle regulatory factor (MRF) 4 is normally the last of the four MRFs to be expressed. To analyze how the timing of MRF4 expression affects muscle regeneration, we compared regeneration after local freeze injury of muscles from wild-type mice with muscles from transgenic mice in which MRF4 expression was under control of an ϳ1.6-kb fragment of the myogenin promoter. Three days after injury, masseter and tibialis anterior (TA) muscles in wild-type mice expressed little or no MRF4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…We were not surprised to find no modulation of Mrf4 myogenic factor at the stages of regeneration selected in this study, since Mrf4 expression has been reported in the later stages of regeneration [31]. The same could also to be true for the myogenin protein level, where the lack of protein modulation may depend on the early observation window selected.…”
Section: Discussionmentioning
confidence: 62%
“…We were not surprised to find no modulation of Mrf4 myogenic factor at the stages of regeneration selected in this study, since Mrf4 expression has been reported in the later stages of regeneration [31]. The same could also to be true for the myogenin protein level, where the lack of protein modulation may depend on the early observation window selected.…”
Section: Discussionmentioning
confidence: 62%
“…This negative effect of altered MRF-4 activation on muscle differentiation is also apparent in muscle regeneration in vivo. Overexpression of MRF4 in a transgenic mouse line caused defective muscle regeneration following injury (85). Presumably, any regulatory role played by p38 in muscle regeneration following injury can be attributable to the p38␣ isoform; genetic ablation of all other p38 isoforms had no effect on muscle fiber growth during regeneration following CTX injection (92).…”
Section: Do Neutrophil-derived or M1 Macrophage-derived Molecules Modmentioning
confidence: 99%
“…IL-4 can also contribute to shifting macrophages from the cytotoxic M1 phenotype to the M2c phenotype that promotes tissue repair (30,31). However, IL-4 can also have direct effects on muscle regeneration, by promoting satellite cell activation and differentiation (42,85). Thus, M2 macrophages can play a central role in regulating regeneration in mdx dystrophy by attenuating the potentially cytolytic M1 phenotype and acting directly on satellite cells to drive their function in muscle repair.…”
Section: Do Immune Cells Regulate Muscle Repair and Regeneration In Cmentioning
confidence: 99%
“…The elevated expression and activity of p38 late in muscle differentiation leads to increased MRF4 phosphorylation and, as a consequence, a decline in desmin and skeletal -actin expression [165]. In fact, overexpression of MRF4 in a transgenic mouse line caused defective muscle regeneration following injury [166]. Therefore, TNF--dependent signaling regulates various aspects of the muscle regenerating process (immune response, and proliferation and differentiation of satellite cells) through different downstream mediators (NF-κB, JNK, and p38) [ Figure 2].…”
Section: Tnf-signalingmentioning
confidence: 99%